ERYTHROCYTES AS A MODEL FOR STUDYING THE EFFECT OF TEMPERATURE ON THE RESISTENCE OF CELLULAR MEMBRANES (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
In this work the effect of different temperatures on erythrocyte resistance has been studied. It was also examined the influence of various temperatures on optic density change of erythrocyte suspension. It was shown that there are no sharp changes of optic density values of erythrocyte suspension, based on which we assume that under the effect of the given temperatures the significant alterations are not observed, but the state of erythrocytes changes, particularly the structure of erythrocyte membranes changes. It was also revealed that the structural changes of erythrocyte membranes occur under the impact of environmental factors, including anthropogenic ones.
Keywords: erythrocyte suspension; acidic hemolysis; stability; erythrocyte aging; optic density